High-efficiency cloning of full-length cDNA. - Okayama, H (1982)
A widely recognized difficulty of presently used methods for cDNA cloning is obtaining cDNA segments that contain the entire nucleotide sequence of the corresponding mRNA. The cloning procedure described here mitigates this shortcoming. Of the 10(5) plasmid-cDNA recombinants obtained per microgram of rabbit reticulocyte mRNA, about 10% contained a complete alpha- of beta-globin mRNA sequence, and at least 30 to 50%, but very likely more, contained the entire globin coding regions. We attribute the high efficiency of cloning full- or nearly full-length cDNA to (i) the fact that the plasmid DNA vector itself serves as the primer for first- and second-strand cDNA synthesis, (ii) the lack of any nuclease treatment of the products, and (iii) the fact that one of the steps in the procedure results in preferential cloning of recombinants with full-length cDNA's over those with truncated cDNA's.